The The Weigert – Meyer Law of Ureteral Duplication: A rare pathological entity - S, Sudhamani; Kumar, Sonal Hemanth; Bhalekar, Surekha; Roplekar, Prakash (Annals of Pathology and Laboratory Medicine, 2019)
Ureteral duplication is a developmental anomaly leading to many complications in children. The Weigert-Meyer law states that ‘In a complete ureteral duplication, the ureter whose orifice is more medial and caudal reaches the upper moiety and the other ureter whose orifice is more lateral and cephalad reaches the lower renal moiety’. This law has been observed universally in cases of ureteral duplication. The possible complications of double ureter and duplex system include obstruction, lithiasis, ureterocele and vesico-ureteral reflux. Hence it is important to recognize this entity for early intervention and to prevent complications. We are publishing one such rare case in a 10 month old child with review of literature.